2021
DOI: 10.1038/s41525-021-00170-3
|View full text |Cite
|
Sign up to set email alerts
|

Ethnic-specific association of amylase gene copy number with adiposity traits in a large Middle Eastern biobank

Abstract: Studies assessing the impact of amylase genes copy number (CN) on adiposity report conflicting findings in different global populations, likely reflecting the impact of ancestral and ethnic-specific environment and lifestyle on selection at the amylase loci. Here, we leverage population size and detailed adiposity measures from a large population biobank to resolve confounding effects and determine the relationship between salivary (AMY1) and pancreatic (AMY2A) amylase genes CN and adiposity in 2935 Qatari ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 46 publications
0
8
0
Order By: Relevance
“…This population-based study showed a significant negative association between SAL and BMI but no association of AMY1 diploid CNs and GWAS-lead SNV with BMI. Although findings regarding the association of AMY1 CNV with BMI or obesity have been inconsistent in populations worldwide [ 13 , 19 21 ], this study joins a list of studies that have demonstrated that AMY1 diploid CN is not associated with BMI. Given that no BMI-associated signals within or near the amylase locus have been found in previous GWASs for BMI using SNVs in East Asian populations, including Japanese populations [ 37 , 42 ], it seems unlikely that salivary amylase AMY1 CNV has a large enough effect on BMI in the Japanese population.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…This population-based study showed a significant negative association between SAL and BMI but no association of AMY1 diploid CNs and GWAS-lead SNV with BMI. Although findings regarding the association of AMY1 CNV with BMI or obesity have been inconsistent in populations worldwide [ 13 , 19 21 ], this study joins a list of studies that have demonstrated that AMY1 diploid CN is not associated with BMI. Given that no BMI-associated signals within or near the amylase locus have been found in previous GWASs for BMI using SNVs in East Asian populations, including Japanese populations [ 37 , 42 ], it seems unlikely that salivary amylase AMY1 CNV has a large enough effect on BMI in the Japanese population.…”
Section: Discussionmentioning
confidence: 85%
“…Although diploid CN of AMY1 can explain some (~10–35%) of the interindividual variations in amylase levels [ 14 17 ], the remaining unexplained phenotypic variation suggests the presence of additional genetic factors. Over the last few decades, many studies have reported consistent findings of negative correlations between amylase levels or amylase activity and obesity-related traits [ 6 , 18 ], but there remains controversy regarding the association of AMY1 CN with obesity or BMI [ 13 , 19 21 ]. Elucidating the complex genetic architecture underlying the amylase levels will provide a deeper understanding of the role of amylase in susceptibility to various diseases and evolutionary adaptation in humans [ 12 , 15 , 19 , 22 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…This duplication was not observed in over 2500 unrelated parents of autism probands, sequenced by an Illumina platform and with CNV calls based on same read depth pipeline 16 , or in the Database of Genomics Variants (DGV) gold-standard dataset (23,300 subjects of various ethnicities) 17 , whereas Genome Aggregation Database -Structural Variants (gnomAD-SV) v2.1 (14,891 subjects) 12 includes only a larger (131 kb) and ultra-rare duplication overlapping this locus (allele frequency ~0.00005). We additionally assessed the occurrence of any structural variation disrupting the LRBA gene in an internal database of 6941 genomes of predominantly Arab/ Middle Eastern ethnicities, sequenced to a minimum of 30x depth 18 , but could not detect any. Inspection of the read alignments (BAM file) suggested more accurate coordinates for the duplication, demarcated by sharp transition of read depth, and that the duplication occurs in tandem (see Fig.…”
Section: Whole-genome Sequencing Variant Identificationmentioning
confidence: 99%
“…Genetic research has also been pivotal in identifying the association of lifestyle with certain conditions [4,5]. Similar advancements have also been reported from the Qatar Genome Project, where genetic variants have been identi ed at the population level, some of which are associated with ethnic-speci c risk of disease development or drug metabolism [6][7][8][9]. In addition to these populationbased biobanks, there are also disease-speci c and project-speci c biobanks.…”
Section: Introductionmentioning
confidence: 98%